2019
DOI: 10.4314/rjmhs.v2i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal pain management among nurses and midwives at two Kigali hospitals

Abstract: BackgroundThe care of high-risk neonates in intensive care units is a relatively new field in resource-limited countries. Consequently, pain management of neonates has not been included or considered as part of neonatal care. Neonatal pain is more difficult to assess than adult pain, as they are unable to self-report. Nurses and midwives caring for neonates have a professional responsibility to recognise and manage neonatal pain. ObjectivesTo assess the knowledge, attitude, and practice of nurses and midwives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 24 publications
9
37
4
Order By: Relevance
“…This was in contrast with the studies done in Rwanda and Brazil which reported that the majority of participants always use more than one non-pharmacological intervention to relieve pain in new-borns. 14 , 15 From the current study, the uses of comfort measures give the impression not understandable as an essential role of nurses. It might be result in ineffective neonatal pain management with comfort.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This was in contrast with the studies done in Rwanda and Brazil which reported that the majority of participants always use more than one non-pharmacological intervention to relieve pain in new-borns. 14 , 15 From the current study, the uses of comfort measures give the impression not understandable as an essential role of nurses. It might be result in ineffective neonatal pain management with comfort.…”
Section: Discussionmentioning
confidence: 73%
“…The proportion means of nurses’ knowledge and practice regarding neonatal pain management were taken from a previous related study conducted in Uganda since there is no related previous study in Ethiopia; they were 61.74% and 52.08%, respectively. 14 A 95% confidence level with 0.05 margin of error was assumed.…”
Section: Methodsmentioning
confidence: 99%
“…The perceptions and nursing practices of pain management in the NICU are of interest to clinicians and researchers worldwide ( Akuma & Jordan, 2012 ;Khoza & Tjale, 2014 ;Muteteli et al, 2019 ). Adequate assessment requires appropriate and valid instruments supported by satisfactory psychometric properties in different languages such as French.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Barriers to the implementation of effective interventions by nurses have been identified in recent studies. These include negative attitudes and lack of knowledge about pain in preterm infants ( Muteteli et al, 2019 ), as well as the absence of opportunities for continuing education ( Mohamadamini et al, 2017 ). Thus, examining nurses' perceptions of pain management practices for preterm infants is essential to offer insights on nursing practices that should be promoted in the NICU.…”
mentioning
confidence: 99%
See 1 more Smart Citation